ANALISA PENGGUNAAN MEDIA SOSIAL SEBAGAI SARANA DIGITAL MARKETING PADA KOMUNITAS USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI KECAMATAN BABAT - Aditya Wahyu Nugroho; Erna Nur Faizah; Rizky Wahyudha Rosiawan (Politeknik Negeri Ambon, 2025)
Introduction: Information technology has an impact on all sectors of life. Social media has now become a trend in marketing communication. Currently, micro, small and medium enterprises (MSMEs) must be able to adapt to modern marketing patterns so as not to be outdated. This research aims to describe how the use of social media in micro, small and medium enterprises (MSMEs) in Babat District. Methods: In this study, the researcher used a type of qualitative research using data collection techniques in the form of observations, questionnaires and interviews. This research was conducted in one of the communities in Babat District. To check the validity of the data taken, the data triangulation technique was used. Results: The result of this study is that the majority of micro, small and medium enterprises (MSMEs) actors who are members of the Preneur community (Preneur Megilan Lamongan) still use WhatsApp social media as the main social media for digital marketing activities. All respondents use WhatsApp to communicate with customers and promote products/services. In addition to being easy to use, micro, small and medium enterprises (MSMEs) actors can also create special groups and send product catalogs to their loyal customers Keywords: Social Media, Digital Marketing, MSMEs